Type I Interferons in the Pathogenesis of Tuberculosis: Molecular Drivers and Immunological Consequences - Donovan, Meg L.; Schultz, Thomas E.; Duke, Taylor J.; Blumenthal, Antje (Frontiers in Immunology, 2017)
Tuberculosis (TB) remains a major global health threat. Urgent needs in the fight against TB include improved and innovative treatment options for drug-sensitive and -resistant TB as well as reliable biological indicators that discriminate active from latent disease and enable monitoring of treatment success or failure. Prominent interferon (IFN) inducible gene signatures in TB patients and animal models of M. tuberculosis infection have drawn significant attention to the roles of type I IFNs in the host response to mycobacterial infections. Here we review recent developments in the understanding of the innate immune pathways that drive type I IFN responses in mycobacteria-infected host cells and the functional consequences for the host defense against M. tuberculosis, with a view that such insights might be exploited for the development of targeted host-directed immunotherapies and development of reliable biomarkers.